Pembelajaran IPA Berbasis Lingkungan Sekitar Dalam Mengembangkan Keterampilan Proses Siswa SD/MI - Siti Mastiyah (TA'DIBAN, 2025)
This study aims to describe the implementation of science learning based on the surrounding environment in developing students’ process skills. This type of research uses a literature study approach. The data collection techniques used include various literature sources and other documentation materials. The results of this study indicate that the implementation of science learning based on the surrounding environment can be carried out in two ways: inside the classroom and outside the classroom. The components involved in developing students’ process skills include observing, communicating, measuring, interpreting and drawing conclusions, predicting, and using tools and materials.